The Challenge of Expanding Secondary Education and Training in Madagascar - World Bank (Washington, DC: World Bank, 2012)
Madagascar is making significant progress in achieving its Education for All Initiative (EFA) goals of providing universal primary education. It has recently decided to initiate far-reaching reforms in its primary and secondary education cycles. Good quality primary graduates are necessary for entry into the secondary education cycles in Madagascar. But equally important is the quality and relevance of what is taught and learned in secondary schools. This is one of the keys for accelerated economic growth and effective social development. International global trends in secondary education provide a useful framework for undertaking the current reform in secondary education. Madagascar's labor market needs more and better secondary graduates with "modern knowledge and better skills" to make its economy competitive and to attract overseas investments in the country. Asia and Latin America have already shown the way. However, to make the expansion of post-primary education services in Madagascar sustainable the system should become much more efficient and produce better results (in terms of quality and quantity). This report is designed to contribute to ongoing education reform discussions by presenting: analysis of the secondary education and training system; challenges and constraints to the expansion of the system; options to expand and improve secondary education based on other country experiences; and possible next steps for identifying the most appropriate course of action. This report aims to encourage discussion among policymakers, stakeholders, and donors, and does not promote one approach over another. To promote a more competitive economy in Madagascar in the 21st century, the government expects to increase the average years of schooling from the current 4.5 years to about 9-10 years by 2015 for the relative age groups. This report discusses the ongoing reform and its impact and provides suggestions for implementation. This report is intended to be used as a discussion instrument and to be disseminated among Madagascar's stakeholders in education.